Micropatterning of BiVO4 Thin Films Using Laser‐Induced Crystallization. Issue 4 (16th December 2015) - Trzciński, Konrad; Rodriguez, Raul D.; Schmidt, Constance; Rahaman, Mahfujur; Sawczak, Mirosław; Lisowska‐Oleksiak, Anna; Gasiorowski, Jacek; Zahn, Dietrich R. T.
Abstract : Relatively high temperatures even up to 500 °C are required to obtain bismuth vanadate (BiVO4 ) films with the scheelite monoclinic (s‐m) structure that shows the highest photocatalytic activity. This requirement limits the possible choice of substrates. Moreover, high quality thin layers of crystalline BiVO4 cannot be prepared with current methods. In this study a light‐induced crystallization approach is presented, which is a step toward preparation and patterning of BiVO4 (s‐m) films for applications on plastic substrates. Thin films of amorphous BiVO4 are prepared by pulsed laser deposition. The possibility of using green (514.7 nm) laser illumination for crystallization of BiVO4 is investigated. The laser‐induced phase transition is tracked using Raman spectroscopy. The results are compared with those obtained from thermally annealed samples, crystalline structure of which is confirmed by measuring X‐ray diffraction. The homogeneity and quality of crystallization are verified using micro‐Raman spectroscopy imaging, while time‐dependent experiments reveal the crystallization rate. The conductivity of the crystallized region is investigated using conductive atomic force microscopy. A strong increase in the conductivity is found in the patterned regions. Experimental results demonstrate the possibility of using the laser‐induced crystallization of BiVO4 to prepare patterns of improved conductivity and semiconducting properties in comparison to amorphous surroundings. Abstract : The possibility of light‐induced crystallization and micropatterning of amorphous bismuth vanadate (BiVO4 ) is presented. The photocrystallization process is tracked in situ using Raman spectroscopy. The conducting properties of amorphous and crystalline BiVO4 are determined using conducting atomic force microscopy. The micropatterned regions exhibit higher conductivity. The photocrystallization process leads to crystallites with scheelite monoclinic structure, which can be applied in photocatalysis.